Valences and Informational Limits of the Financial Statements Prepared by Romanian Smes in the New Resilient Context: Array - Zuca, Marilena; Munteanu, Victor; Soare, Janina; Danescu, Magdalena; Tinta, Alice; Paduraru (Horaicu), Adriana (Acta Universitatis Danubius. Œconomica, 2022)
The analysis and interpretation of the financial-accounting information presented in the financial statements of an entity have played a special role over the years and are the subject of numerous studies and articles. The objective of this article is to provide an analysis of the potential relations between financial-accounting information and the visibility of SMEs' activity. In this context, we tried to show that: 1. the analysis of the financial-accounting information provided by SMEs is a relevant and effective tool for the social partners; 2. information provided by SMEs adds value to their activity in terms of sustainable development and social responsibility, in the context of the digitalisation of the economy and society; and 3. external communication of information provided by SMEs contributes to the reactivity of public authorities to their needs.